Comparative Analysis of Actual Costs and INA-CBGs Tariffs for Hemodialysis Services at Haji Abdul Manan Simatupang Regional General Hospital - Ayu Puspita; Ani Nuraini; Eka Yoshida (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Outpatient hemodialysis is a high-cost chronic service that may generate a gap between actual hospital costs and the INA-CBGs reimbursement tariff under the JKN scheme. This study aimed to calculate the unit actual cost of outpatient hemodialysis, compare it with the INA-CBGs tariff, identify dominant cost components, and explore managerial strategies to address cost discrepancies. A mixed-methods approach was conducted at RSUD Haji Abdul Manan Simatupang from January to September 2025, combining quantitative cost and service-volume analysis with qualitative semi-structured interviews. Normality was tested using Shapiro–Wilk and differences were analyzed using the Wilcoxon signed-rank test. A total of 4,810 sessions were recorded, with total actual costs of IDR 4,193,552,621 and an average unit cost of IDR 871,840 per session, exceeding the INA-CBGs tariff of IDR 841,900. The average gap was IDR 29,940 per session, with deficits in 7 of 9 months. The difference was statistically significant (p=0.021). Consumables (BMHP) were the primary cost driver (60%). Strategic responses included consumable cost control, standardized clinical pathways, digital monitoring, capacity optimization, strengthened claims management, and capital planning. These findings highlight the need for strengthened cost governance to ensure financial sustainability and service quality.